Impact of chronological age on efficacy and safety of fluoropyrimidine plus bevacizumab in older non-frail patients with metastatic colorectal cancer: a combined analysis of individual data from two phase II studies of patients aged >75 years. (25th April 2022) - Moriwaki, Toshikazu; Nishina, Tomohiro; Sakai, Yoshinori; Yamamoto, Yoshiyuki; Shimada, Mitsuo; Ishida, Hiroyasu; Amagai, Kenji; Sato, Mikio; Endo, Shinji; Negoro, Yuji; Kuramochi, Hidekazu; Denda, Tadamichi; et al.
Abstract: Objective: Many clinical trials for older patients with metastatic colorectal cancer have been conducted, and fluoropyrimidine and bevacizumab are standard treatments. However, the relationship between age and the efficacy and safety of this treatment is unclear in older metastatic colorectal cancer patients. Methods: Individual data from two phase II studies on older (≥75 years), non-frail patients with metastatic colorectal cancer treated with uracil-tegafur/leucovorin or S-1 combined with bevacizumab were collected. Patient characteristics were evaluated with multiple regression analyses for survival outcomes, using the Cox proportional hazard model and linear regression analyses for the worst grade of adverse events. Results: We enrolled 102 patients with a median age of 80 years (range, 75–88 years). Of the 70 patients who died, seven (10%) died of causes unrelated to disease or treatment. The study treatment was discontinued due to adverse events in 19 patients (18.6%), with 63% aged ≥85 years. The adverse event that most commonly resulted in treatment discontinuation was grade 2 fatigue (21%). Chronological age was not associated with progression-free survival (Hazard ratio, 1.03; P  = 0.40) or overall survival (Hazard ratio, 1.02; P  = 0.65). Age was weakly associated with non-hematologic adverse events (regression coefficient [R], 0.27; P  = 0.007), especially fatigue (R, 0.23; P  = 0.02) and nausea (R, 0.19; P  = 0.06), but not with hematologic (R, 0.05; P  = 0.43) or bevacizumab-related (R, −0.06; P  = 0.56) adverse events. Conclusions: The efficacy of fluoropyrimidine plus bevacizumab was age-independent in patients with metastatic colorectal cancer aged ≥75 years, and attention should be paid to non-hematologic adverse events as age increases. Abstract : In patients with metastatic colorectal cancer aged ≥75 years, the efficacy of fluoropyrimidine plus bevacizumab was age-independent, but attentions should be paid to non-hematologic adverse events as age increases.